Why more males? Differences in entrepreneurial intentions of male and female university students and graduates - Ulrike Köpke; Eva Schmitt-Rodermund (Journal of Global Entrepreneurship Research, 2025)
The persistently lower participation of women in entrepreneurial activities constitutes a significant economic and societal problem. This study investigates the entrepreneurial intentions (EI) of university students and graduates from the University of Applied Sciences Potsdam from a gender-specific perspective, with the central aim of identifying the reasons for the continuing differences in EIs between men and women. The theoretical framework is based on the Theory of Planned Behavior (TPB), which was extended in this study by the construct of entrepreneurial self-identity to gain a more comprehensive understanding of EI. Using structural equation modeling, an analysis was conducted for the entire cohort as well as stratified by gender, examining how attitude, social norms, perceived behavioral control, and entrepreneurial self-identity influence EI. The results of the online survey, in which 414 students and graduates participated between June 2nd and July 14th, 2023, show that men exhibit significantly higher EIs than women. Furthermore, it was demonstrated that risk-taking propensity contributes to these gender differences. Moreover, perceived behavioral control and parental role models proved to be crucial determinants for the EIs of women, while these factors did not significantly relate to the intentions of men. The analysis underscores the complexity of gender differences in EIs and implies that considering gender-specific factors in targeted support measures for universities can help reduce gender differences and thus better leverage the entrepreneurial potential of women.
Keywords: 330; Entrepreneurial intentions; Gender; University of Applied Sciences; Personality; Entrepreneurial self-identity